2018
DOI: 10.1007/s00330-018-5623-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of scoring hip osteoarthritis with MRI (SHOMRI) scores using hip arthroscopy as a standard of reference

Abstract: Purpose To validate SHOMRI gradings in preoperative hip magnetic resonance imaging (MRI) with intra-arthroscopic evaluation of intraarticular hip abnormalities. Methods Preoperative non-arthrographic 3.0-T MRIs of 40 hips in 39 patients (1 patient with bilateral hip surgery) with femoroacetabular impingement (FAI) syndrome (mean age, 34.7 years ± 9.0; n = 16 females), refractory to conservative measures, that underwent hip arthroscopy were retrospectively assessed by two radiologists for chondrolabral abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…New semiquantitative scoring systems have recently been developed and validated for use in OA research studies to assess the severity of structural pathology in other joints. These include the Shoulder Osteoarthritis Severity Score (SOAS) for the shoulder joint 57 , Scoring Hip Osteoarthritis with Magnetic Resonance Imaging (SHOMRI) for the hip joint 58,59 , and Thumb Osteoarthritis MRI Score (TOMS) for the first carpometacarpal joint 60 . These new scoring systems have been shown to have high construct validity and high inter-observer agreement for assessing the severity of structural joint pathology on MRI.…”
Section: Scoring Systems For Oamentioning
confidence: 99%
“…New semiquantitative scoring systems have recently been developed and validated for use in OA research studies to assess the severity of structural pathology in other joints. These include the Shoulder Osteoarthritis Severity Score (SOAS) for the shoulder joint 57 , Scoring Hip Osteoarthritis with Magnetic Resonance Imaging (SHOMRI) for the hip joint 58,59 , and Thumb Osteoarthritis MRI Score (TOMS) for the first carpometacarpal joint 60 . These new scoring systems have been shown to have high construct validity and high inter-observer agreement for assessing the severity of structural joint pathology on MRI.…”
Section: Scoring Systems For Oamentioning
confidence: 99%
“…In contrast, previous studies showed, that CT-based 3D-models allow exact surgical planning [ 8 , 9 ] of hip arthroscopy [ [10] , [11] , [12] , [13] ] for FAI or periacetabular osteotomy [ 2 ] for DDH. But CT scans should not be used for young patients due to the radiation exposure [ 14 ], especially in patients of child-bearing age.…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage abnormalities were scored on a range from 0 to 2, where 0 represents no cartilage lesion, 1 a partial‐thickness cartilage lesion, and 2 a full thickness lesion. The SHOMRI method has been validated with arthroscopic findings and was found to be a reliable and valid method to assess cartilage abnormalities 20 …”
Section: Methodsmentioning
confidence: 99%